CRM Systems and their effects on Business Performance - Aphale, Apoorv (2008)
The business world today is in a middle of huge transition. From brand and product centric, the organizations are striving to become customer centric. This has put customer to the central of all the operations of the organization. This has brought forward the concept of relationship marketing where companies do not look at the customer from single transaction perspective, but want to establish a long term relationship with their customers. Relationship Marketing has further evolved into customer relationship management popularly known as CRM. Customer relationship management helps the companies to manage the huge amount of data available to them about the customer, so that they know customer better and can customize their offerings with respect to individual customer. Technology has proved to be a boon for companies implementing CRM strategies. Technology has enabled the managers and executives to handle each customer as a single entity, thus creating a detailed database of customer's every contact with the company. This has given way for CRM systems, which facilitate the customer retention and acquisition by cutting down the costs on both these aspects, thus influencing the profitability and overall business performance of the organizations. A lot of investment is required for successful implementation of such systems and past research has shown that the failure rate of CRM systems is very high and organizations fail in their CRM efforts. This research looks forward to investigate whether the investment in CRM technology is actually justified and that CRM system is not a hype and that does it really contribute to the overall business performance of the organizations?